(untitled) (Praxis Educativa, 2012)
This article deals with the power and ideology question as well as their implications to develop a discourse which articulates, production of meanings with subjectivity, identity and difference, in relation to education. The subject matter is approached from the theoretical framework of critical pedagogy, specifically its two-dimensional conception of power, and the relations it keeps with the ideological processes of construction of subjectivity and the possibilities of resistance and counter-hegemony in education.